Tuturan Perintah Guru dalam Pembelajaran Bahasa Indonesia dengan Metode Ceramah Plus Tanya Jawab dan Tugas (CPTT) di SD Negeri 01 Maguan - Widi Sukmawati Trisnatul Rohma; Arti Prihatini (Institut Agama Islam Negeri Curup, 2022)
The teacher's orders are verbal tactics used to condition the learning process and encourage students to do something. This study aims to determine the types and functions of teacher orders in class IV in Indonesian language subjects at SD Negeri 01 Maguan, Malang Regency and describe the application, advantages, and disadvantages of the lecture method plus questions and answers and assignments (CPTT) used by teachers. The study used a qualitative descriptive design with an ethnographic communication approach. The source of the research data is the speech of the fourth-grade Indonesian teacher at SDN 01 Maguan, Malang Regency. Data were collected by using observation, recording, and recording techniques. The data analysis technique was carried out by recording all the speeches of teachers and students in class IV SDN 01 Maguan, analyzing, and classifying the speech data of teacher orders related to the lecture method plus questions and answers and assignments. The results showed that there were 4 types of command utterances in the form of imperative sentences of orders, requests, appeals, and invitations. The CPTT method is used to provide some knowledge to students so that the learning process can take place effectively and efficiently. The use of the CPTT method shows its advantages, namely that teachers can directly measure the level of understanding of students through the question-and-answer process and assignments. And there is a weakness that students become passive because learning is centered on the teacher's lecture